PEMANFAATAN CANDI DERES SEBAGAI SUMBER BELAJAR IPS UNTUK MENINGKATKAN MOTIVASI DAN KEMAMPUAN BERPIKIR KRITIS MURID DI SMPN 2 GUMUKMAS KABUPATEN JEMBER - Arif, Syarifuddin (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study aims to examine the effectiveness of utilizing a local historical site, Candi Deres, as a learning resource to enhance students’ motivation and critical thinking skills in Social Studies (IPS) at SMPN 2 Gumukmas, Jember Regency, Indonesia. Employing a qualitative case study approach, data were collected through literature review, participatory observation, in-depth interviews, open-ended questionnaires, and focus group discussions (FGD). Data analysis was conducted through stages of data condensation, data display, and conclusion drawing/verification, using content analysis, discourse analysis, and interpretive analysis methods. The findings reveal that integrating Candi Deres into the learning process significantly increases student engagement and motivation, fosters reflective inquiry, cultivates cultural awareness, and promotes critical thinking regarding socio-historical contexts. Furthermore, the study highlights a pedagogical transformation among teachers, who began to adopt more contextual and collaborative teaching strategies. This research underscores the importance of place-based and culturally rooted education as a relevant and strategic approach to implementing the Merdeka Curriculum and strengthening students' character development. The theoretical and practical implications contribute to enriching Social Studies pedagogy oriented toward local wisdom and 21st-century competencies.